PENERAPAN ANTARMUKA DINAMIS PADA APLIKASI AKADEMIK BERBASIS ANDROID UNTUK DOSEN KASUS: UNIVERSITAS INDO GLOBAL MANDIRI - Mustafa Ramadhan; Evi Yulianti (Jurnal Informatika Global)
The application interface currently used by Indo Global Mandiri University was designed for wide screen on desktop and laptop computers.When the application opens on a smaller screen smartphone and or tablet, app components, such as combo boxes, tables, etc. cut off on the right side so users have to shift it horizontally to the left. In addition, the displayed text is hard to read because of its smaller size. Indeed, users can zoom in but as a result the text is not displayed intact, there is a section of text that is cut off because of the limited screen. Users should not only shift the view vertically, but also horizontally. This certainly reduces the convenience of using the application. Therefore, for smartphone and tablet users, the app needs to be remodeled by adjusting its interface so it is more convenient and easier to use. The size and resolution of smartphones and tablet screens that are very diverse is a challenge in itself. The built interface must dynamically adjust the display format automatically according to the screen size and resolution. The design approach is usually by: (1) responsive design, or (2) adaptive design. The application will be built using a combination of both by optimizing the size and resolution of the existing screen so it is expected that the resulting interface provides convenience for the user. Coding uses Java programming language with Android Studio IDE 3. Applications can be used by UIGM lecturers as alternatives of existing applications.Keywords : User interface, Responsive design, Adaptive design